Genetic diversity of sugarcane (Saccharum Officinarum L.) based on morphological characters - Intan Poespita Windiyani; Mahfut Mahfut (Genetikawan Muda Indonesia, 2021)
Sugarcane (Saccharum officinarum L.) is an important plantation crop in the commercial sector as it accounts for 65% of worldwide sugar production. The role of sugarcane is very important in the sugar industry, so it needs to be supported by intensive research, especially for the breeding and assembly of superior varieties to improve the quality and quantity of sugarcane production. The process of plant breeding cannot be separated from the germplasm management program, because it is a source of genetic diversity of a plant species. Characteristics and evaluation of nuftah plasma are one of the activities carried out to determine the potential characteristics of the breeding program. One of the efforts to extract information in empowering the nuftah plasma collection is by morphological characteristics, so that superior plant varieties or accessions can be classified. Morphological characters were observed qualitatively and quantitatively. Each variety of a sugarcane species has a specific morphological description, both quantitative and qualitative traits, then the data base for these characteristics is used as a reference for filtering potentially superior to diversity in germplasm collections.